Stakeholders prioritization of climate-smart agriculture (CSA) in the rice-based production systems of Mali - Dossou-Yovo, Elliott Ronald; Arouna, Aminou; Bryan, Elizabeth; Ringler, Claudia; Futakuchi, Koichi; Grosjean, Godefroy; Mujawamariya, Gaudiose; Benfica, Rui; Freed, Sarah; Rodrigue, Yossa (Accelerating Impacts of CGIAR Climate Research for Africa, 2021)
Agriculture, food and nutrition security, and the livelihoods of millions of people are affected by climate change. Given the scarce resources of most of the West African countries, there is a need to prioritize the technologies that need to be taken at scale to mitigate the climate change impacts. This study uses a stakeholders prioritization framework to assess the locally suitable interventions in the diverse rice-based production systems in Mali. The prioritization was made in two steps. First, all interventions were evaluated by stakeholders based on their climate-smart performance indicator (ability to increase farm productivity, income, and resilience and reduce greenhouse gas emission). Second, the interventions were evaluated based on their implementation feasibility (technical feasibility, cost, gender inclusivity, demand by the market, and alignment with the social and cultural context). The technologies’ CSA performance indicator was more determined by their ability to increase farm productivity and income, while their implementation feasibility was more driven by their technical feasibility and cost of implementation. Best bet CSA technologies and practices with high CSA performance indicator and high implementation feasibility score were RiceAdvice, submergence tolerant varieties, integrated rice – vegetable, and mechanical thresher in the irrigated lowland; submergence tolerant varieties, drought-tolerant varieties, RiceAdvice, and ASI thresher in the rainfed lowland; drought-tolerant varieties and RiceAdvice in the rainfed upland, and submergence tolerant varieties and RiceAdvice in the submergence system. This study shows the potential of using a stakeholders prioritization framework to inform investment in climate change adaptation and mitigation at the local level.